2020
DOI: 10.1590/1413-812320202510.2.26882020
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with delay in diagnosis and mortality in patients with COVID-19 in the city of Rio de Janeiro, Brazil

Abstract: We investigated the predictors of delay in the diagnosis and mortality of patients with COVID-19 in Rio de Janeiro, Brazil. A cohort of 3,656 patients were evaluated (Feb-Apr 2020) and patients’ sociodemographic characteristics, and social development index (SDI) were used as determinant factors of diagnosis delays and mortality. Kaplan-Meier survival analyses, time-dependent Cox regression models, and multivariate logistic regression analyses were conducted. The median time from symptoms onset to diagnosis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 18 publications
2
29
0
16
Order By: Relevance
“…Another factor on the basis of the capacity of the health system is the national rates of ICU beds per 10 000 inhabitants, where the north and northeast regions have the worst national scores, with 0.9 beds per 10 000 inhabitants in the north and 1.5 per 10 000 inhabitants in the northeastern regions [ 26 ]. Besides, the high mortality identified especially in the areas can be justified by conditions related to health care, socioeconomic and demographic conditions, and factors intrinsic to the population (age, presence of comorbidities and life habits) [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another factor on the basis of the capacity of the health system is the national rates of ICU beds per 10 000 inhabitants, where the north and northeast regions have the worst national scores, with 0.9 beds per 10 000 inhabitants in the north and 1.5 per 10 000 inhabitants in the northeastern regions [ 26 ]. Besides, the high mortality identified especially in the areas can be justified by conditions related to health care, socioeconomic and demographic conditions, and factors intrinsic to the population (age, presence of comorbidities and life habits) [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…No studies about this delay in COVID-19 diagnosis have been described before in ARDs and even in the general population there is a scarcity of data. A systematic review which examined predictors of hospitalization for COVID-19 in ARD patients found few studies exploring this variable [ 47 ] and the data currently available are still controversial [ 48 50 ]; however, this variable could be critical in terms of mortality if the health system collapses or is near collapse; for example, a low level of oxygen saturation at admission has been found to be associated with mortality in a recent Peruvian study; once again a delay in hospitalization of about 8 days since initial symptoms was observed in that study [ 51 ]. We considered our results to be of the utmost importance in the care of patients with ARDs in the community.…”
Section: Discussionmentioning
confidence: 99%
“…Coronavirus disease (COVID-19) remains an emergency of global interest; up to 21 May 2021, a total of 164.52 million confirmed cases and 3.42 million deaths had accumulated from the disease [ 1 ]. Social disparity and the scarcity of hospital resources for the treatment of patients in hospital units have been identified among the main factors associated with an increased number of deaths from this disease [ [2] , [3] , [4] , [5] , [6] , [7] ]. Thus, it is essential to identify potential prognostic biomarkers towards earlier and more targeted care, especially considering that some patients with COVID-19 develop severe disease, which is associated with a higher risk of hospitalisation.…”
Section: Introductionmentioning
confidence: 99%